Integrative Review Of Nurse–Pharmacist–Midwife Interventions To Improve Medication Adherence And Self-Management Among Diabetic Patients (The Review of Diabetic Studies, 2025)
Background:Diabetes mellitus is a global health challenge that requires continuous pharmacological and behavioral management. Poor medication adherence and inadequate self-management remain leading causes of uncontrolled blood glucose and diabetes-related complications. Collaborative care involving nurses and pharmacists has emerged as a promising approach to address these challenges through comprehensive patient education, therapeutic optimization, and follow-up.Aim:This integrative review aimed to evaluate the effectiveness of nurse–pharmacist collaborative interventions in improving medication adherence and self-management behaviors among diabetic patients.Methods:Following Whittemore and Knafl’s (2005) framework, an integrative review was conducted across PubMed, Scopus, CINAHL, and Web of Science databases for studies published between 2015 and 2025. Eligible studies included quantitative, qualitative, and mixed-method research examining interventions jointly implemented by nurses and pharmacists for patients with type 1 or type 2 diabetes. Data were extracted, appraised using the Joanna Briggs Institute (JBI) checklists, and synthesized thematically.Results:Twenty-three studies met the inclusion criteria. Five key themes emerged: (1) collaborative education and counseling for medication adherence, (2) medication review and therapeutic optimization, (3) empowerment and self-management support, (4) barriers and facilitators to collaboration, and (5) clinical and behavioral outcomes. Evidence indicated that joint nurse–pharmacist interventions significantly improved medication adherence (15–25 %), reduced HbA1c levels by 0.5–1.4 %, and strengthened patients’ self-efficacy and engagement in diabetes care.Conclusion:Integrating nursing and pharmacy expertise offers a holistic, patient-centered model that enhances both adherence and self-management outcomes. Implementation of structured nurse–pharmacist programs, supported by clear policies and shared documentation systems, could substantially improve diabetes outcomes—particularly within Saudi Arabia’s Vision 2030 framework for preventive and multidisciplinary healthcare.